The influence of mordenite characteristics in mordenite mixed with alumina on cracking of vacuum gas oil - Lee, KH; Lee, YW; Kim, JD; Jeon, KS; Ha, BH (KOREAN INST CHEM ENGINEERS, 1997)
Catalytic cracking of vacuum gas oil has been investigated at 500 degrees C over mixed catalysts in a micro-activity tester. The catalyst consists of mordenite treated by either HCl/steam or HF and alumina prepared at pH of 9.5 or 7.8. The catalysts retaining mordenite in which SiO2/Al2O3 weight ratio ranged from 15 to 20 show the maximum activity and selectivity for gasoline. Both the activity and selectivity for gasoline seem to depend strongly on both acid strength of mixed catalysts and mesopore volume of the mordenite. It is found, however, that the selectivity of kerosene+diesel in liquid product as well as the yield of aromatics in gasoline are influenced more by mesopore volume of mordenite than by acid properties of mordenite in the catalyst of mordenite/alumina.
Keywords: CATALYSTS